Investigation of Stress Intensity Factor Reduction using Steel and GFRP Patches for Repairing Edge Cracks in Steel Plates - Jassam, Zainab Najih; Laftah, Rafil M. (Basrah Journal for Engineering Sciences, 2024)
The ultimate objective of this study was to compare the performance of repaired edge cracks in steel plates before and after repair with patches made of steel patch and glass fiber-reinforced polymer composite patches (GFRP) in different shapes: circular, rectangular, and trapezoidal, under two conditions: unsymmetric patch (one patch) and symmetric patch (two patches). A three-dimensional finite element model of the one-sided and two-sided repaired examples is used to study how the steel and composite patch affect the stress intensity factor (SIF). Under uniaxial tensile loads, the use of steel patches and GFRP composite patches to repair cracks was studied. The results showed that the steel patch performs better than the GFRP patch because it significantly lowers the stress intensity factor (SIF). The symmetric patch arrangement (two patches) is better than the un-symmetric patch arrangement (one patch) because it significantly reduces the stress intensity factor (SIF).